A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
HELP, PLEASE! FAN and MEDAL
[01.01]
Given the equation 5x − 4 = –2(3x + 2), solve for the variable. Explain each step and justify your process.
Megan solved a similar equation below. Is Megan's solution correct? Explain why or why not.
3(2x − 4) = 5x − 1
6x − 12 = 5x − 1
11x − 12 = –1
11x = 11
x = 11
anonymous
 one year ago
HELP, PLEASE! FAN and MEDAL [01.01] Given the equation 5x − 4 = –2(3x + 2), solve for the variable. Explain each step and justify your process. Megan solved a similar equation below. Is Megan's solution correct? Explain why or why not. 3(2x − 4) = 5x − 1 6x − 12 = 5x − 1 11x − 12 = –1 11x = 11 x = 11

This Question is Open

nkhanfar
 one year ago
Best ResponseYou've already chosen the best response.1its correct because when you change the values from one side to the other they change signs for example if its positive it will change into negative and if its negative it will change into positive dont take my word for it
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.